Adjuvant postoperative radiation therapy for colonic carcinoma. - Willett, C G (1987)
One hundred thirty-three patients with Stage B2, B3, and C colonic carcinoma had resection for curative intent followed by adjuvant postoperative radiotherapy to the tumor bed. The 5-year actuarial local control and disease-free survival rates for these 133 patients were 82% and 61%, respectively. Stage for stage, the development of local regional failure was reduced for patients receiving postoperative radiotherapy compared with a historic control series. Local recurrence occurred in 8%, 21%, and 31% of patients with Stage B3, C2, and C3 tumors who had radiation therapy, respectively, whereas the local failure rates were 31%, 36%, and 53% in patients treated with surgery alone. There was a 13% and 12% improvement in the 5-year disease-free survival rate in the patients with Stage B3 and C3 lesions who had radiotherapy compared with the historic controls. For patients with Stage C disease, local control and disease-free survival rates decreased progressively with increasing nodal involvement; however, local control and disease-free survival rates were higher in the patients who had radiotherapy than in those who had surgery alone. Failure patterns in the patients who had radiotherapy did not show any notable changes compared with those for patients who had surgery alone. Postoperative radiation therapy for Stage B3, C2, and C3 colonic carcinoma is a promising treatment approach that deserves further investigation.